Sustainability and small and medium-sized enterprises lessons from mixed methods research - Factor, Aharon 1965-; Ulhøi, John P. (Routledge, an imprint of the Taylor & Francis Group, 2021)
"Industrialisation has brought great benefits to humankind but now after 200 years of fossil fuel use, land clearance and pollution the planet's boundaries are being stretched to their limits. Going beyond these confines would have severe consequences for humankind. To prevent this happening, government, corporate and community initiatives must focus on reducing the environmental impacts of the 400 million small and medium-sized enterprises (SMEs) given that they produce approximately 70% of the world's pollution, 60% of carbon emissions and have significant impacts on the land. To date, research shows that SMEs have been environmental laggards and more needs to be understood to improve sustainability in the SME sector. Broadening the researcher's methodological focus beyond traditional singular approaches improves knowledge generation and better informs policy and practice. This book paves the way by showing the reader that a mixed-method research design is able to provide a deep, diverse and holistic understanding of sustainability and SMEs. Importantly, the book also provides an in-depth mapping of mixed method sustainability and SME research at a regional level. As this book is about environmental sustainability framed in a business context it will be of interest to researchers, academics, students and those in industry who are enquiring about the environmental sustainability of SMEs."--Provided by publisher.